An improved multi-scale two phase method for bubbly flows. (December 2020) - Zhang, Xiaosong; Wang, Jianhua; Wan, Decheng
Highlights: An improved hybrid VOF/Euler–Lagrange multi-scale two phase method is developed. Comparison is carried out between different critical criteria for the multi-scale transformation. A new curvature-based algorithm is proposed for the VOF to Lagrange transformation. The new method has been proved to be more accurate and efficient for bubble breakup simulation. Abstract: Multiple spatial scale is an important characteristic of two phase flow phenomena. The micro-scale and macro-scale flow structures are obviously different in flow state and have different effects on the mass, momentum and energy transfer between two phases. Different modeling approaches have been developed for each scale physical phenomenon in traditional numerical simulations. However, it is difficult to simulate two phase flow systems with multi-scale flow structures simultaneously. In order to address this problem, a multi-scale two phase method is developed based on the combination of Volume of Fluid (VOF) interface capture method and Euler–Lagrange particle tracking method. The fundamental assumption of the present method is that there is a clear scale separation between VOF interfaces and bubbles. Therefore, VOF method with artificial compressive algorithm is used to simulate the dynamic evolution of macro-scale air-water interface. While Euler–Lagrange method is used to track the micro-scale bubbles that cannot be captured in grids. Collision, coalescence and breakup of Lagrange bubbles and two-way coupling are fully considered to construct a comprehensive micro-bubble solving procedure. Transformation criteria and the corresponding algorithms between micro-scale and macro-scale flow structures are designed and discussed in detail. In addition, a new curvature-based algorithm for the transformation from VOF interface to Lagrange bubbles is proposed. Simulations of typical two phase flow problems involving multi-scale flow transformation are carried out to test the performance of the multi-scale solver. Results indicate that the multi-scale two phase method performs significantly better than the pure VOF method in capturing micro-scale phenomena. Besides, the curvature-based transformation algorithm proposed in this paper is proved to be more precise and efficient than the previous identify-based one. From the perspective of simulation accuracy and efficiency, the multi-scale two phase method is more promising for the simulation of actual complex two-phase flows.